Evaluation of opioid discontinuation after non-orthopaedic surgery among chronic opioid users: a population-based cohort study. (March 2020) - Jivraj, Naheed K.; Scales, Damon C.; Gomes, Tara; Bethell, Jennifer; Hill, Andrea; Pinto, Ruxandra; Wijeysundera, Duminda N.; Wunsch, Hannah
Abstract: Background: Many patients use opioids chronically before surgery; it is unclear if surgery alters the likelihood of ongoing opioid consumption in these patients. Methods: We performed a population-based matched cohort study of adults in Ontario, Canada undergoing one of 16 non-orthopaedic surgical procedures and who were chronically using opioids, defined as (1) an opioid prescription that overlapped the index date and (2) either a total of 120 or more cumulative calendar days of filled opioid prescriptions, or 10 or more prescriptions filled in the prior year. Each surgical patient was matched based on age, sex, Charlson comorbidity index, and daily preoperative opioid dose to three non-surgical patients who were also chronic opioid users. The primary outcome was time to opioid discontinuation. Results: The cohort included 4755 surgical and 14 265 matched non-surgical patients. After adjustment for sociodemographic characteristics and comorbidities, surgery was associated with an increased likelihood of opioid discontinuation (adjusted hazard ratio: 1.34, 95% confidence interval [CI]: 1.27, 1.42). Among surgical patients, factors associated with a reduced odds of discontinuation included a mean preoperative opioid dose above 90 morphine milligram equivalents (adjusted odds ratio [aOR]: 0.39; 95% CI: 0.32, 0.49) or filling a prescription for oxycodone (aOR: 0.73; 95% CI: 0.56, 0.98). Receipt of an in-patient Acute Pain Service consultation (aOR: 1.34; 95% CI: 1.06, 1.69) or residing in the highest neighbourhood income quintile (aOR: 1.35; 95% CI: 1.04, 1.79) were associated with a greater odds of opioid discontinuation. Conclusions: For chronic opioid users, surgery was associated with an increased likelihood of discontinuation of opioids in the following year compared with non-surgical chronic opioid users.